KEDUDUKAN SUNNAH DAN TIPOLOGI GOLONGAN INKARUSSUNNAH - Muhammad Abdul Rozaq Hidayat (TARBAWI:Journal on Islamic Education, 2023)
Hadith is one of the Islam’s basis of laws. The definition of hadith is a law that based from every Prophet Muhammad’s words, actions, or traits. This makes hadith positioned in second position of law basis after the Holy Qur’an which must be obeyed and faithfully received by all of muslim. However, some of muslim don’t accept hadith as the law basis of Islam. In this journal, qualitative and library research are used for methods in writing this journal. The research also use data collective methods where the data is collected from different sources that is relevant with the topic, such as journal, books, etc. After the data has been collected, an analysis is practiced in order to make this journal’s material stronger and based from the truth. Studying about how strong hadith is will make people more understand about its strength, function, and who receive and refuse it.Keyword : Hadith, function, obey and disobey